Critical Discourse Analysis and Its Implication in English Language Teaching: A Case Study of Environmental News Text - Zhang, Lishi; Jocuns, Andrew (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
English learners are usually taught English in university by focusing on improving learners’ language skills instead of critical aspects of language use. However, critical reading is crucial in English language learning. Critical discourse analysis (CDA) is an approach to deal with the analysis of linguistic features, and the deployment of these linguistic features in the texts can dramatically influence how humans perceive social changes. Accordingly, this study employs CDA in English Language Teaching (ELT), which aims to cultivate students’ critical thinking (CT) and critical language awareness (CLA). The present study integrated CDA into the English reading of English and Translation majors to enhance students’ critical learning. Eighteen students were chosen to attend the training workshops. Six news items were purposively selected as the reading materials for students. After the training, the study found students’ CLA increased, and students were interested in analyzing and criticizing the English language. Furthermore, students were motivated to learn English and equipped with critical thinking skills. The findings imply that deploying CDA for authentic texts (e.g., news outlets) in ELT is effective, and English language teachers can integrate it into daily teaching.